Quasi linear and stone geary utility functions based-internet service financing scheme with marginal costs and monitoring costs - Indrawati, Indrawati; Puspita, Fitri Maya; Yuliza, Evi; Dwipurwani, Oki; Octarina, Sisca; Helmayanti, Rizky (International Journal of Informatics and Communication Technology (IJ-ICT), 2024)
The use of computer network technology is currently increasing, especially on the internet network. To connect to the actual internet, it is a task for internet service provider (ISP). Providing advantages to ISPs, it requires a financing scheme. This study's goal is to present a modified model for internet service financing schemes, within the customer choices and consumer satisfaction levels to maintain the schemes. To achieve the best outcomes, this updated model is built through marginal costs and cost monitoring while taking into account service quality based on stone-geary utility functions and quasi-linear utility functions. This research provides a solution regarding the differences in increasing consumer interest with payment options on model modification that will be provided. Traffic Digilib in a local server in Palembang. According to this study, a usage-based financing strategy and a two-part pricing of IDR 2727.8 per kbps will yield the highest revenues.